2021
DOI: 10.1007/s00704-021-03694-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of heat stress and cloudiness probabilities in post-flowering of spring wheat and canola in the Southern Cone of South America

Abstract: Episodes of heat stress constrain crop production and will be aggravated in the near future according to short and medium-term climate scenarios. Global increase in cloudiness has also been observed, decreasing the incident solar radiation. This work was aimed to quantify the probability of occurrence of heat stress and cloudiness, alone or combined, during the typical post-owering period of wheat and canola in the Southern Cone of South America. Extended climate series (last 3-5 decades with daily register) o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…This behavior clearly shows the greater photoperiod response of carinata in relation to canola as previously reported by Nanda et al (1996), which is expressed in a 77% higher estimated R p coefficient (1.6 vs. 0.9 for carinata and canola, respectively). However, despite the greater cycle adjustment of carinata in relation to canola, for the commercial range of canola sowing date in the region (early to mid-June) (Rivelli et al, 2021), the flowering date of canola occurs, on average, 15 d before carinata, which determines that the harvest date and seeding of the summer crop is delayed in carinata in relation to canola.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This behavior clearly shows the greater photoperiod response of carinata in relation to canola as previously reported by Nanda et al (1996), which is expressed in a 77% higher estimated R p coefficient (1.6 vs. 0.9 for carinata and canola, respectively). However, despite the greater cycle adjustment of carinata in relation to canola, for the commercial range of canola sowing date in the region (early to mid-June) (Rivelli et al, 2021), the flowering date of canola occurs, on average, 15 d before carinata, which determines that the harvest date and seeding of the summer crop is delayed in carinata in relation to canola.…”
Section: Discussionmentioning
confidence: 99%
“…The period from seed emergence to end of juvenile stage is sensitive to vernalization, while the photoperiod‐induced phase occurs between end of juvenile and floral initiation (Robertson & Lilley, 2016). Synchronizing crop phenology with environment is critical to increase crop production (Hunt et al., 2019; Miralles et al., 2001) as well as to reduce potential yield losses caused by extreme temperatures (Chauhan et al., 2019; Kutcher et al., 2010; Rivelli et al., 2021; Takashima et al., 2013). In this sense, modeling crop phenology is of great interest for adapting strategies to climate change in agriculture (Ceglar et al., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Climate-change-induced temperature fluctuations pose a significant threat to crop production, particularly in the Southern Hemisphere, where strong warming is predicted across various global warming scenarios [1][2][3][4]. Recently, Rivelli et al (2021) reported a temperature increase in the Southern Cone of South America over the past 30-50 years, highlighting the urgency of understanding crop responses to these changes [5].…”
Section: Introductionmentioning
confidence: 99%
“…Wheat is one of the three most wide-spread crops in the world, but, unlike rice and corn, both its winter and spring cultivars are widely cultivated. Spring common (bread) wheat, in this respect, mains a crucial crop for the regions of South and North America, Australia, Central and South-East Asia as well as for those of Northern Asia which have harsh continental climate (Morgounov et al, 2018;Garcia et al, 2019;Rivelli et al, 2021).…”
Section: Introductionmentioning
confidence: 99%